Arca Hindu Di Candi Bumi Ayu: Refleksi Keagamaan Hindu Di Masa Sriwijaya - Anggraini, Kesi; Hudaidah (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the Hindu statues found in the Bumiayu temple. The Srivijaya Kingdom was a maritime empire stretching from Southern Thailand to Java. Srivijaya is considered the first maritime empire in the Indonesian archipelago, meaning it occupied a vast territory and controlled the seas and waterways, such as rivers. One of the key areas of Srivijaya's success was the Strait of Malacca. The Strait of Malacca served as a busy international trade route at that time. Srivijaya, with its capital in Palembang, successfully exploited this situation, becoming a bustling port. This bustling port brought various cultural and religious elements to Srivijaya, including its inland areas, one of which is Bumiayu. Bumiayu boasts a unique temple complex that embraces Hinduism, Buddhism, and Tantrism. This demonstrates the strong religious tolerance of Srivijaya, especially Bumiayu. This study aims to identify the Hindu statues found in the Bumiayu Temple Complex and to reconstruct the religious diversity of the Srivijaya Kingdom.